Critical discourse analysis of global warming public service advertisement: implication for students - A'thi Fauzani Wisudawati; Novi Ika Setyani (EduLite: Journal of English Education, Literature and Culture, 2018)
Preventing global warming through advertisement is considered as potential appeal. Since advertisement became one of material taught in the school, the importance not only affects the citizen but also influences how the teachers deliver the material by advertisement media. This study aimed at analyzing 4 non-profit public service advertisements and investigating how governments or advertisers use discourse and semiotics to encourage people to commit global warming avoidance. The four advertisements analyzed are global warming advertisements which have been selected from government’s official website. The methodology adopted in this study is qualitative method. The advertisement is analyzed qualitatively in terms of content. Later on some English teachers have been interviewed to illustrate the implication of advertisement in pedagogical activities. This research finds that the teachers with their foresights can enlighten hidden values in public service advertisements.